Development and in vitro/in vivo evaluation of a novel benznidazole liquid dosage form using a quality‐by‐design approach. Issue 12 (11th October 2017) - Santos Souza, Higo Fernando; Real, Daniel; Leonardi, Darío; Rocha, Sandra Carla; Alonso, Victoria; Serra, Esteban; Silber, Ariel Mariano; Salomon, Claudio Javier
Abstract: Objectives: To develop an alcohol‐free solution suitable for children of benznidazole, the drug of choice for treatment of Chagas disease. Methods: In a quality‐by‐design approach, a systematic optimisation procedure was carried out to estimate the values of the factors leading to the maximum drug concentration. The formulations were analysed in terms of chemical and physical stability and drug content. The final preparation was subjected to an in vivo palatability assay. Mice were infected and treated orally in a murine model. Results: The results showed that benznidazole solubility increased up to 18.38 mg/ml in the optimised co‐solvent system. The final formulation remained stable at all three temperatures tested, with suitable drug content and no significant variability. Palatability of the preparation was improved by taste masking of BZL. In vivo studies showed that both parasitaemia and mortality diminished, particularly at a dose of 40 mg/kg/day. Conclusion: Quality by design was a suitable approach to formulate a co‐solvent system of benznidazole. The in vivo studies confirmed the suitability of the optimised such solutions to diminish both parasitaemia and mortality. Thus, this novel alternative should be taken into account for further clinical evaluation in all age ranges.